2018
DOI: 10.1182/blood-2018-09-874107
|View full text |Cite
|
Sign up to set email alerts
|

Unique dependence on Sos1 in KrasG12D-induced leukemogenesis

Abstract: Abstract We and others have previously shown that KrasG12D is a much more potent oncogene than oncogenic Nras in hematological malignancies. We attributed the strong leukemogenic activity of KrasG12D at least partially to its unique capability to hyperactivate wild-type (WT) Nras and Hras. Here, we report that Sos1, a guanine nucleotide exchange factor, is required to mediate this process. Sos1 is overexpressed in KrasG12D/+ cells, but not in NrasQ61R/+ and NrasG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…SOS1 could act as an oncogene and play an important role in cancers (25,26). You et al (27) suggested that SOS1 was relevant to leukemogenesis. Moreover, SOS1 has been found to affect RAS/MAPK and PI3K/AKT pathways to regulate various cellular processes (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…SOS1 could act as an oncogene and play an important role in cancers (25,26). You et al (27) suggested that SOS1 was relevant to leukemogenesis. Moreover, SOS1 has been found to affect RAS/MAPK and PI3K/AKT pathways to regulate various cellular processes (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Oncogenic RAS mutations have been identified in a variety of hematologic malignances, such as juvenile myelomonocytic leukemia, chronic myelomonocytic leukemia, AML, and MPN [79]. A recent knock-in mouse study showed that the Kras G12D mutation drives the aggressive MPN phenotype through mediation of Sos1, a guanine nucleotide exchange factor [80,81]. The authors suggested that the survival of patients with KRAS mutations may increase with therapies that target the Sos1-oncogenic Kras interaction [81].…”
Section: Mutations In Signal Transduction Genesmentioning
confidence: 99%
“…A recent knock-in mouse study showed that the Kras G12D mutation drives the aggressive MPN phenotype through mediation of Sos1, a guanine nucleotide exchange factor [80,81]. The authors suggested that the survival of patients with KRAS mutations may increase with therapies that target the Sos1-oncogenic Kras interaction [81].…”
Section: Mutations In Signal Transduction Genesmentioning
confidence: 99%
“…All animal experiments were conducted in accordance with the Guide for the Care and Use of Laboratory Animals and approved by an Animal Care and Use Committee. For lineage analysis of PB and BM, flow cytometric analyses were performed as described (You et al, 2018). Stained cells were analyzed on a LSR II flow cytometer (BD Biosciences).…”
Section: Genetically Engineered Mouse Modelsmentioning
confidence: 99%
“…Surface proteins were detected with FITCconjugated antibodies (eBioscience unless specified) against B220 (RA3-6B2), Gr-1 (RB6-8C5), CD3 (17A2, Biolegend), CD4 (GK1.5), CD8 (53-6.7), and TER119 (TER-119), and PEconjugated anti-CD117/c-Kit (2B8) antibody. To analyze phospho-ERK1/2, total BM cells were deprived of serum and cytokines and then stimulated with cytokines as previously described (You et al, 2018). Phosphorylated ERK1/2 (p-ERK1/2) was analyzed in defined Lin -/low c-Kit + cells as described.…”
Section: Genetically Engineered Mouse Modelsmentioning
confidence: 99%